Commercial Pressures on Professionalism in American Medical Care: From Medicare to the Affordable Care Act. Issue 4 (December 2014) - Marmor, Theodore R.; Gordon, Robert W.
<x xml:space="preserve">Abstract</x> Since the passage of Medicare, the self‐regulation characteristic of professionalism in health care has come under steady assault. While Canadian physicians chose to relinquish financial autonomy, they have enjoyed far greater professional autonomy over their medical judgments than their U.S. counterparts who increasingly have their practices micromanaged. The Affordable Care Act illustrates the ways that managerial strategies and a market model of health care have shaped the financing and delivery of health care in the U.S., often with little or no evidence of their effectiveness.